Comparison of pointwise encoding time reduction with radial acquisition (PETRA) imaging with conventional MR imaging for the diagnosis of traumatic fractures in children - Xiamei Zhuang; Ke Jin; Xiaoming Li; Junwei Li; Yan Yin; Zhang Huiting; Hong Liu; Meitao Liu (BMC Medical Imaging)
Abstract Purpose This study aimed to determine whether adding pointwise encoding time reduction with radial acquisition (PETRA) images to conventional magnetic resonance (MR) imaging improves the depiction and characterization of traumatic fractures in pediatric patients. Methods Twenty-nine pediatric subjects with fractures and a control group of twenty individuals without fractures were included. Two independent observers assessed conventional MR, PETRA, and combined MRI + PETRA images, documenting the presence of fractures, bone fragments, callus formation, displacement, size, and angles of fractures. Results Diagnostic accuracy was higher for combined conventional MR with PETRA images than for conventional MR or PETRA alone in detecting fractures (area under curve (AUC): 0.86 for conventional MR, 0.97 for PETRA, 1.00 for combined), callus formation (AUC: 0.67 conventional MR, 0.82 PETRA, 0.86 combined), and bone fragments (AUC: 0.89 conventional MR, 0.96 PETRA, 0.97 combined). PETRA images improved agreement in detecting fractures, especially in the ulna/radius (κ = 0.46 conventional MR, 1.00 PETRA, 1.00 combined) and fibula/talus (κ = 0.42 conventional MR, 1.00 PETRA, 1.00 combined), compared to CT. PETRA also enhanced agreement in characterizing callus formation, bone fragments, displacement, size and fracture angles (intraclass correlation > 0.88 for all comparisons), compared to CT. Addition of PETRA images revealed that the differences in the measurements of fragment displacement, size, and fracture angle compared to CT, were not statistically significant (all p > 0.05). Conclusion Adding PETRA images to conventional MR enhances diagnostic accuracy and reliability in detecting fractures among pediatric patients compared to conventional MR alone. Clinical trial number Not applicable.